2011
DOI: 10.4012/dmj.2010-097
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of MC3T3-E1 on poly(4-styrenesulfonic acid-co-maleic acid)sodium salt-coated films

Abstract: Polyelectrolyte multilayer (PEM) film can modify the surface properties of materials to improve cellular responses. In this study poly(diallyldimethylammonium chloride) (PDADMAC), poly(sodium 4-styrene sulfonate) (PSS) and poly(4-styrenesulfonic acid-comaleic acid) sodium salt (PSS-co-MA) were assembled into PEM {(PDADMAC/PSS)4/PDADMAC+PSS-co-MA} film on glass surfaces and its ability on affecting osteoblast functions were examined. PSS-co-MA film showed an increase roughness and more wettable surface as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…One major requirement of any tissue engineering scaffold is biocompatibility, which is the ability to support normal cellular activity without any toxic effects to the host tissue (Williams, 2008). The biocompatibility of DTS and CETC were evaluated using MC3T3-E1 cells, an immortalized murine preosteogenic cell-line commonly used to assess in vitro osteogenic development (Angwarawong, Dubas, Arksornnukit, & Pavasant, 2011). When seeded on DTS and CETC, MC3T3-E1 cells attached and proliferated well, as shown by the increasing metabolic activity over time in the Alamar blue assay (Figure 3b) as well as the spreading of cells in SEM ( Figure 3a).…”
Section: In Vitro Characterization Of Dts and Cetcmentioning
confidence: 99%
See 1 more Smart Citation
“…One major requirement of any tissue engineering scaffold is biocompatibility, which is the ability to support normal cellular activity without any toxic effects to the host tissue (Williams, 2008). The biocompatibility of DTS and CETC were evaluated using MC3T3-E1 cells, an immortalized murine preosteogenic cell-line commonly used to assess in vitro osteogenic development (Angwarawong, Dubas, Arksornnukit, & Pavasant, 2011). When seeded on DTS and CETC, MC3T3-E1 cells attached and proliferated well, as shown by the increasing metabolic activity over time in the Alamar blue assay (Figure 3b) as well as the spreading of cells in SEM ( Figure 3a).…”
Section: In Vitro Characterization Of Dts and Cetcmentioning
confidence: 99%
“…In osteogenic media, MC3T3-E1 cells would undergo osteogenic differentiation, which involves the phases of proliferation, maturation, and eventually mineralization (Owen et al, 1990). These phases could be identified by the upregulation of osteogenic genes, the increased production of osteogenic proteins, and the production of mineralized matrix (Angwarawong et al, 2011). Among the various osteogenic genes, BSP, OC, and OPN were used as markers to investigate osteogenic differentiation in this study.…”
Section: In Vitro Characterization Of Dts and Cetcmentioning
confidence: 99%
“…Poly(NaSS) plays an important role in the production of this enzyme [38] and that effect was reflected in all tested conditions. Its influence was the most significant for the combination Col I ?…”
Section: Differentiation and Mineralizationmentioning
confidence: 89%
“…[38,39] In our study, we synthesized a novel biologically PTH-related peptide, PTHrP-1, and examined its dose-dependence on the osteogenic induction of MC3T3-E1 cells in vitro, which could improve the proliferation and differentiation of MC3T3-E1 cells and maintained their morphology. However, Zhang et al [40] reported that 3 different cell models were utilized for differentiation studies in vitro in order to determine whether there was variability among cell lines or there were cell type-specific effects.…”
Section: Discussionmentioning
confidence: 99%